Discovering the technical terms on digital learning transformation in the COVID-19 era - Abdurrakhman Prasetyadi; D.W. Ari Nugroho; Aria Bisri; Fitria Laksmi Pratiwi; Jazuli; Penny Sylvania Putri (Berkala Ilmu Perpustakaan dan Informasi, 2022)
Introduction. The pandemic has triggered researchers to measure the success of the methods and platforms used in digital learnings. This study aims to discover technical terms in the study of digital learning transformation in the COVID-19 era. Data Collection Methods. Using the Web of Science (WoS) database to search and collect publication data on digital learning transformation in the COVID-19, this paper collected 432 articles from November 2019 to August 2021. Data Analysis. The data were descriptively analyzed using bibliometric and text analysis by applying clustering to the paper dataset. Results and Discussion. The results of this study show three technical field clustersand terms in digital learning transformation studies. These include virtual clinical trials, emergency remote learning, and image augmentation.. In addition, this paper show a collaborative network of authors and countries in the study of digital transformation in the COVID-19 era. Conclusion.Many new terms have been obtained in the transformation of digital learning studies in the COVID-19 era, which is not only “online learning”.